A literature review: Does expressive writing effective to reduce stress? - Savera, Nikhen Dea; Purwaningrum, Ribut; Hidayat, Rian Rokhmad (ProGCouns: Journal of Professionals in Guidance and Counseling, 2022)
The study used a literature review method to describe the findings of articles related to the practice of expressive writing in reducing stress. The data was obtained from 30 selected studies consisting of 13 national journals and 17 international articles. The data collection technique was a documentation study in which the data was analyzed by using content analysis.  The results of the study were: (1) expressive writing could reduce the stress of a wide range of ages from children to adults, and was able to help problems from various types of stress disorders; (2) expressive writing could be flexibly applied with a various number of sessions and different durations according to the counselee's need; (3) expressive writing effectively reduced and overcome stress in general, academic stress, depression problems combined, symptoms of post-traumatic stress, stress during the pandemic, and stress on children with HIV/AIDS. The study results recommended that school counselors could utilize expressive writing to reduce the negative impacts of stress by creatively modifying the relevant intervention based on the findings. Further research is expected to explore and expand the study through literature studies from another perspective such as focusing on research methods with various variables, subjects, objects, and locations.